PERAN ORANG TUA DALAM MENANGANI ANAK AUTIS (STUDI KASUS 4 KELUARGA ANAK AUTIS DI KOTA PEKANBARU) - Merianto, Randi Wahyu; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted in Special Schools Children Self. The purpose of this study was to Describing the characteristics of children with autism and how to determine the role of parents in dealing with children with autism. In this study the authors collected data to descend directly into the field and do the interview technique to place the research location. Respondents in this study consists of 4 families. The data obtained was processed in the form of descriptive qualitative analysis. The conclusion of this study is in general it is not easy for parents to accept reality when their child are stated having autism. This mental attitude which can accept the reality often impact on the inability of parents to adjust to the situation of children. Whereas autism require a very complex treatment and requires active participation of parents in many ways related to the therapy.The results of this study indicate that there was a significant correlation between parental adjustment and their role in autism therapy. So concern for parents of children with autism is very important, because with the better parent to acceptance and adjustment to their child is expected to be the better their active role in various efforts to the treatment of autism.Keywords: Characteristics, Role, Parents